Intonation pattern as factor influencing non-speakers' attitudes towards Singaporean Hokkien vis-à-vis Singaporean Cantonese - Lai, Zi Xuan (2019)
Existing studies on the Chinese vernaculars in Singapore focus more on language shift and semantic changes, while not much has been done in comparing the attitudes of people towards the different Chinese languages. Singaporean Hokkien is often perceived to sound more “vulgar” as compared to Singaporean Cantonese. While such association may arise from the prevalent usage of Singaporean Hokkien in swearing, other factors, such as intonation patterns, may influence how people view the Chinese vernaculars instead. This study seeks to investigate whether the intonation patterns of Singaporean Hokkien influence non-speakers to rate it less favourably as compared to Singaporean Cantonese. 18 non-Chinese participants (females = 9, males = 9) participated in a matched-guise test where they rated speakers of the two Chinese languages on 25 personal attributes, which were subsequently grouped into four different traits. Results show that the male participants rated more traits favourably for the Singaporean Cantonese speaker while female participants rated the Singaporean Hokkien speaker better. The split in results does not provide significant evidence in confirming the hypothesis that Singaporean Hokkien speakers are perceived less positively than the Singaporean Cantonese speakers. Greater phonetic analysis and qualitative interviews could be done to investigate further into the issue.